Impact of screen use on behavior and sleep in patients with autism spectrum disorder - Lima, Matheus Eugênio de Sousa; Lopes, Lívia Maria Eugênio; Lima, Fernanda Eugênio de Sousa (Arquivos de Neuro-Psiquiatria, 2025)
The increasing screen time among the pediatric population is a detrimental factor for cognitive and psychosocial development, especially for children with autism spectrum disorder (ASD). However, there are still many questions regarding its negative effects on behavior and sleep in this population group and, as of the writing of this study, there are no specific recommendations regarding screen use for children with ASD.To synthesize and analyze the current evidence on the association between screen exposure time, behavioral symptoms, and sleep disorders in ASD children.The authors provided a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist adapted review of studies that examined the association between screen time and both autistic symptoms and sleep disturbances in this patient population.Research indicates that excessive screen use among ASD children, particularly in preschool-aged children, may be associated with significant behavioral, emotional, and sleep quality impacts. The screen time recommendations set by the World Health Organization for the general pediatric population could also be applied to these children, at least until new studies can clarify specific guidelines, taking their particularities into account.This review article explores the current evidence on the association between excessive screen time and both autistic symptoms and sleep disturbances in ASD, underscoring the relevance of further clinical investigation.
Keywords: Autistic Disorder; Cell Phone Use; Internet Use; Sleep Wake Disorders